Antiviral activity of triazine analogues of 1-(S)-[3-hydroxy-2-(phosphonomethoxy)propyl]cytosine (cidofovir) and related compounds - Krecmerová, Marcela; Holý, Antonín; Pískala, Alois; Masojídková, Milena; Andrei, Graciela; Naesens, Lieve; Neyts, Johan; Balzarini, Jan; De Clercq, Erik; Snoeck, Robert (Journal of medicinal chemistry, 2007)
Treatment of 5-azacytosine sodium salt with diisopropyl [(2-chloroethoxy)methyl]phosphonate followed by removal of ester groups with BrSi(CH3)3 afforded 1-[2-(phosphonomethoxy)ethyl]-5-azacytosine (3). Reaction of 5-azacytosine with [(trityloxy)methyl]-(2S)-oxirane followed by etherification with diisopropyl (bromomethyl)phosphonate and removal of ester groups gave 1-(S)-[3-hydroxy-2-(phosphonomethoxy)propyl]-5-azacytosine (1). The synthesis of 6-azacytosine congener 2 was analogous using N4-benzoylated intermediates. Compound 1 was shown to exert strong activity against a broad spectrum of DNA viruses including adenoviruses, poxviruses, and herpesviruses (i.e., herpes simplex viruses, varicella zoster virus, and human cytomegalovirus). Decomposition of 1 in alkaline solutions resulted in products 17 and 18. While the N-formylguanidine derivative 17 proved active, the carbamyolguanidine derivative 18 was devoid of antiviral activity.
Keywords: triaziny; Cell Line; DNA viry; cytosin; Cercopithecus aethiops; RNA-viry; Retroviridae; Stereoisomerism; Cidofovir; antivirové látky; Mice; Triazines; Organophosphonates; stereoizomerie; zvířata; vztahy mezi strukturou a aktivitou; Humans; cidofovir; RNA Viruses; Cytosine; myši; DNA Viruses; buněčné linie; Chlorocebus aethiops; Antiviral Agents; organofosfonáty; Structure-Activity Relationship; lidé; Animals